2015
DOI: 10.1002/anie.201508495
|View full text |Cite
|
Sign up to set email alerts
|

Direct Trifluoromethylthiolation and Perfluoroalkylthiolation of C(sp2)H Bonds with CF3SO2Na and RfSO2Na

Abstract: A new method for CF3SO2Na-based direct trifluoromethylthiolation of C(sp(2))-H bonds has been developed. CF3SSCF3 is generated in situ from cheap and easy-to-handle CF3SO2Na, and in the presence of CuCl can be used for electrophilic trifluoromethylthiolation of indoles, pyrroles, and enamines. The method has been extended to perfluoroalkylthiolation reactions using RfSO2Na.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(77 citation statements)
references
References 85 publications
2
75
0
Order By: Relevance
“…They consist in nanocrystals with 2-10 nm diameters and made up of groups [12][13][14][15] elements (e.g. ZnS, CdS, CdSe, PbSe, InAs, or InP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They consist in nanocrystals with 2-10 nm diameters and made up of groups [12][13][14][15] elements (e.g. ZnS, CdS, CdSe, PbSe, InAs, or InP).…”
Section: Introductionmentioning
confidence: 99%
“…The field is fairly new, Cdots having been discovered in 2004 and quantitative and comparative data are still scarce, but the carbon particles appear to be biocompatible, non-toxic, easily derivatizable, and their fluorescence properties can be tuned by modifying their size and/or surface. Moreover the 2-photon cross section of C-dots is quite large so that they can be conveniently excited at 800 nm, opening the way to their use in drug release and photodynamic treatment (PDT) of cancer [11,12]. Carbon nanoparticles can also be involved in FRET processes and are able to sensitize the luminescence of Ln III ions [13].…”
Section: Introductionmentioning
confidence: 99%
“…The direct introduction of functional groups to heterocyclic molecules to get useful heterocyclic derivatives without prefunctionalization is an attractive synthetic strategy. 7 When we tried to perform the trifluoromethylthiolation of imidazo [1,2-a]pyridine with CF 3 SO 2 Na, an unexpected methylene-bridged product bis(2phenylimidazo [1,2-a]pyridin-3-yl)methane (2a) was obtained in 55% yield. 4 Extensive studies for the functionalization of imidazopyridines on the same position were reported in recent years, in which most efforts were focused on introducing sulfur-5 or fluorine-containing groups 6 for the consideration of the potential application in pharmaceutical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, inspired by the fluorous-tagging idea, we prepared recyclable organocatalysts fluorous hydrazine-1,2-bis(carbothioate) 1 and hydrazine-1,2-dicarboxylate 2 (Scheme 1) and then applied them to the synthesis of β-chloroethers under mild reaction conditions [7][8][9]. The catalytic reaction proceeded smoothly, and with the aid of fluorous silica gel, these fluorous compounds could be recovered easily by fluorous solid-phase extraction (F-SPE) and no environmentally harmful perfluosolvents were used [13][14][15][16][17][18][19][20][21][22]. …”
Section: Introductionmentioning
confidence: 99%